Anodic Determination of Acetylsalicylic Acid at a Mildly Oxidized Boron-Doped Diamond Electrode in Sodium Sulphate Medium. (21st June 2011) - Cofan, Codruţa; Radovan, Ciprian
Abstract : Differential pulse voltammetry (DPV) and chronoamperometry (CA) were used to detect and determine acetylsalicylic acid (ASA) at a mildly oxidized boron-doped diamond (BDD) electrode in a neutral sodium sulphate solution as supporting electrolyte. ASA determination in unbuffered medium was achieved using neutralized standard and real samples. Over the concentration range of 0.01 mM–0.1 mM, linear calibration plots of anodic current peaks in DPV and anodic currents in CA experiments versus concentration were obtained with very high correlation coefficients and good sensitivity values. The limits of detection were situated around 1 μ M. The association of DPV and CA techniques with standard addition method represented a suitable option for the determination of ASA in real samples such as pharmaceutical formulations.